2022
DOI: 10.1155/2022/5740971
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Landscape of HOXA2, HOXA9, and HOXA10 as Potential Biomarkers for Predicting Progression and Prognosis in Prostate Cancer

Abstract: Prostate cancer (PCa) is recognized as a common malignancy in male patients. The homeobox A cluster (HOXA) family members have been confirmed to be implicated in the development of several types of tumors. However, the expression pattern and prognostic values of HOXA genes in PCa have not been investigated. In this study, we analyzed TCGA datasets and identified six HOXA family members which showed a dysregulated expression in PCa specimens compared with nontumor specimens. We also explored the potential mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Even more surprisingly, this function was most enriched for HOXA2 although prostate cancer is more often associated to the deregulated activity of posterior HOX members (see below). However, recent work showed that HOXA2 was associated with aggressive prostate cancer, underlining the robustness of our data (Gao P, et al, 2018; Xia JH, et al, 2018; Song YP., et al, 2022).…”
Section: Resultssupporting
confidence: 83%
“…Even more surprisingly, this function was most enriched for HOXA2 although prostate cancer is more often associated to the deregulated activity of posterior HOX members (see below). However, recent work showed that HOXA2 was associated with aggressive prostate cancer, underlining the robustness of our data (Gao P, et al, 2018; Xia JH, et al, 2018; Song YP., et al, 2022).…”
Section: Resultssupporting
confidence: 83%
“…To understand these dynamics, it is imperative to establish an association between the expression levels of various genes and immune infiltrating molecules. It has been reported that during the progression of prostate cancer (PCa), aberrantly expressed HOXA2, HOXA9, and HOXA10 facilitate the infiltration of dendritic cells, macrophages, and mastocytes [ 80 ]. In EOC, HOXA9 facilitates the transcriptional activation of TGF-β2, which in turn triggers the efflux of chemokines such as CXCL12, IL-6, and VEGF-A in peritoneal fibroblasts [ 73 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low-methylation epigenotype of HOXA2 and HOXA9 in squamous cell carcinoma was associated with idiopathic pulmonary fibrosis and poorer prognosis ( Hata et al, 2020 ). In another study on prostate cancer, HOXA2, HOXA9, and HOXA10 were identified as critical genes, which were both abnormally expressed and associated with clinical outcomes of patients with prostate cancer ( Song et al, 2022 ). In addition to cancers, the CpG methylation of HOXA2 was related to severe fibrosis and the progression in hepatitis B-related chronic liver disease ( Zeybel et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%